Shaping the Digital Transformation in Latin America : Strengthening Productivity, Improving Lives. (OECD Publishing, 2019)
This report discusses policies and approaches to spur sustainable and inclusive digital transformation in the LAC region across seven action areas: enhancing access to digital technologies; strengthening their effective use; enabling digital innovation; ensuring quality jobs for all; promoting an inclusive digital society; strengthening trust; and fostering market openness. The report also aims to contribute to the preparation of an action plan that will support the region's efforts to reap the benefits of the digital transformation.This publication was prepared to support the discussions of the OECD Latin America and the Caribbean Regional Programme's Third Ministerial Summit on Productivity "Harnessing the Digital Transformation to Boost Productivity in in Latin America and the Caribbean". It draws on OECD work on carried out in the context of the Going Digital project, as well as a range of work specific to the LAC region, such as the OECD-IDB report Broadband Policies for Latin America and the Caribbean, the OECD Reviews of Telecommunication Policies in Mexico and Colombia, and the OECD Going Digital Reviews of Colombia and Brazil.